Impact of Electronic Commerce on the role of the middleman. - Chan, Jamie Pei Ee. (2008)
More businesses are being conducted through e-commerce which provides a direct interface between the supplier and customer. Now that the supplier can communicate directly with the consumer, what will be the impact of this on the middleman? We have done an exploratory study on this topic.